Resolution of cassava-infecting alphaflexiviruses: Molecular and biological characterization of a novel group of potexviruses lacking the TGB3 gene - Lozano, Ivan; Leiva, Ana M.; Jimenez, Jenyfer; Fernández Huaytalla, Elizabeth; Carvajal Yepes, Monica; Cuervo, Maritza; Cuellar, Wilmer J. (El Sevier, 2022)
9 páginas